A rare clinic entity: Huge trichobezoar - Hamidi, Hidayatullah (Int J Surg Case Rep, 2016)
INTRODUCTION: Trichobezoar is a rare clinical entity in which a ball of hair amasses within the alimentary tract. It can either be found as isolated mass in the stomach or may extend into the intestine. Trichobezoars mostly occur in young females with psychiatric disorders such as trichophagia and trichotillomania. CASE REPORT: Authors present a giant trichobezoar in an 18 year old female presented with complaints of upper abdominal mass, epigastric area pain, anorexia and weight loss. The patient underwent trans-abdominal ultrasonography (USG), Computed tomography (CT), upper gastrointestinal endoscopy and subsequently laparotomy. USG was inconclusive due to non-specific findings. It revealed a thick echogenic layer with posterior dirty shadowing extending from the left sub-diaphragmatic area to the right sub hepatic region obscuring the adjacent structures. Abdominal CT images revealed a huge, well defined, multi-layered, heterogeneous, solid appearing, non-enhancing mass lesion in the gastric lumen extending from the gastric fundus to the pyloric canal. An endoscopic attempt was performed for removal of this intraluminal mass, but due to its large size, and hard nature, the endoscopic removal was unsuccessful. Finally the large trichobezoar was removed with open laparotomy. CONCLUSION: Trichobezoars should be suspected in young females with long standing upper abdominal masses; as the possibility of malignancy is not very common in this age group. While USG is inconclusive, trichobezoar can be accurately diagnosed with CT. In patient with huge trichobezoar, laparotomy can be performed firstly because of big size and location of mass, and psychiatric recommendation should be made to prevent relapse of this entity.